2009
DOI: 10.1017/s136898000999187x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight and obesity among Kenyan pre-school children: association with maternal and early child nutritional factors

Abstract: Objective: To report on the prevalence of overweight and obesity among preschool children in Kenya and examine the associations between childhood overweight and selected maternal and child-related factors. Design: Demographic Health Survey data, multistage stratified cluster sampling methodology. Setting: Rural and urban areas of Kenya. Subjects: A total of 1495 children between the ages of 3 and 5 years in Kenya. Results: Over 30 % of the children were stunted, approximately 16 % were underweight, 4 % were wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
100
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(117 citation statements)
references
References 33 publications
16
100
1
Order By: Relevance
“…For example, a comparison of children born small for gestational age compared with children having average birth weights indicated that although the two groups had similar body composition at birth and similar BMI by age 3 or 4 years, children who were small at birth had higher percentage body fat and more abdominal fat than those with average birth weight (51) . A similar study indicated that infants who were stunted had a 70% increase in odds of being overweight at age 3–5 years (54) . This is particularly problematic in transitional societies where undernutrition and continued infectious disease burdens contribute to lower weight and shorter length at birth.…”
Section: Discussionmentioning
confidence: 94%
“…For example, a comparison of children born small for gestational age compared with children having average birth weights indicated that although the two groups had similar body composition at birth and similar BMI by age 3 or 4 years, children who were small at birth had higher percentage body fat and more abdominal fat than those with average birth weight (51) . A similar study indicated that infants who were stunted had a 70% increase in odds of being overweight at age 3–5 years (54) . This is particularly problematic in transitional societies where undernutrition and continued infectious disease burdens contribute to lower weight and shorter length at birth.…”
Section: Discussionmentioning
confidence: 94%
“…Families of affected infants should be counseled on appropriate feeding practices and other preventive interventions (21). Intrauterine, infant, and preschool periods are considered possible critical periods for programming long-term regulation of energy balance (22)(23)(24). Waiting for school programs to address this problem is probably too late.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the determinants of child nutritional status in Subsaharan Africa (Gewa, 2009;Zivin et al, 2009;Alderman, 2007 Alderman (2007) and Ssewanyana (2003). To support program setting at the local and national levels, this study was conducted to identify urban-rural differences in the magnitude and determinants of under five child undernutrition in Ethiopia by using the 2011 EDHS data.…”
Section: Discussionmentioning
confidence: 99%